2013
DOI: 10.1590/s1984-29612013000400007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alternate and simultaneous grazing on endoparasite infection in sheep and cattle

Abstract: This experiment was carried out on 8 ha of Panicum maximum cv. Tanzania pastures, with rotational grazing consisting of 7 days of occupation and 21 days of rest. Four treatments were evaluated: cattle grazing alone (BOV), sheep grazing alone (OVI), cattle and sheep grazing simultaneously (SIM) and cattle grazing followed by sheep (alternate - ALT). Twenty heifers and 30 male Santa Inês lambs were used. Fecal egg count (FEC) and fecal cultures were carried out. Blood was also collected to examine red and white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…While our results are thus likely influenced by regional context, they also provide the first indication that the cograzing of horses and cattle has beneficial effect for equine strongyle control. Our results are consistent with previous observations in ruminant farming, showing that simultaneous grazing by cattle and sheep (Southcott and Barger, 1975;Giudici et al, 1999;Marley et al, 2006;Brito et al, 2013), alternate grazing with cattle and sheep (Rocha et al, 2008) or mixed grazing by cattle and goats (Mahieu, 2013) reduce parasitic infection in lambs and goat kids. Because our survey was designed to characterize both types of farming systems with a number of similar characteristics between farms, it was not possible to sample the whole range of equine-to-cattle ratio.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While our results are thus likely influenced by regional context, they also provide the first indication that the cograzing of horses and cattle has beneficial effect for equine strongyle control. Our results are consistent with previous observations in ruminant farming, showing that simultaneous grazing by cattle and sheep (Southcott and Barger, 1975;Giudici et al, 1999;Marley et al, 2006;Brito et al, 2013), alternate grazing with cattle and sheep (Rocha et al, 2008) or mixed grazing by cattle and goats (Mahieu, 2013) reduce parasitic infection in lambs and goat kids. Because our survey was designed to characterize both types of farming systems with a number of similar characteristics between farms, it was not possible to sample the whole range of equine-to-cattle ratio.…”
Section: Discussionsupporting
confidence: 93%
“…Because of the relative host specificity of parasitic helminths, each grazing species is assumed to act as a dead-end for the parasites infecting members of the other species. The so-called 'dilution effect' has been successfully implemented with cattle and sheep, whereby lamb parasite burden was significantly reduced (Marley et al, 2006;Brito et al, 2013), and with cattle and goats; strongyle egg excretion by Creole kids grazed on irrigated pastures was significantly reduced by sequential grazing with heifers (Mahieu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The pasture composition is presented in Table 1. Further details are to be found in Brito et al (2013).…”
Section: Methodsmentioning
confidence: 99%
“…This questions the use of anthelmintics for horses, and calls for alternative methods to control strongyles. Many studies demonstrated that associating cattle and sheep in mixed grazing systems successfully controlled nematode infection in sheep (Brito et al, 2013;Marley et al, 2006). On mixed farms, horses and cattle are frequently grazed together.…”
Section: Methodsmentioning
confidence: 99%